Differences in Bleed Sedimentation Rate and Hematocrit Values in Chronic Kidney Failure Patients Examined Before and After Hemodialysis at Tabanan Regional Hospital - I Made Dwipa Cahyana; Heri Setiyo Bekti; I Gede Sudarmanto (MEDICA (International Medical Scientific Journal), 2024)
Chronic Kidney Disease (CKD) is a pathological condition that is irreversible and has various underlying causes. The diagnosis is based on structural or functional abnormalities of the kidneys, with the primary criterion being a glomerular filtration rate (GFR) of less than 60 mL/min/1.73 m² for more than three months. Common symptoms include fatigue, loss of appetite, and muscle cramps. Management of CKD consists of two stages: conservative treatment aimed at slowing disease progression and renal replacement therapy, such as dialysis or kidney transplantation. Erythrocyte Sedimentation Rate (ESR) and Hematocrit (Hct) tests are important for detecting decreased erythropoietin production, which impacts red blood cell formation. The objective of this study was to examine the differences in ESR and Hct values in patients with chronic kidney disease before and after undergoing hemodialysis. The study employed a pre-experimental design using a One-Group Pretest-Posttest approach, involving a single experimental group without a control group. Measurements were taken both before and after the intervention. The results from 10 CKD patients at Tabanan Regional Public Hospital indicated that all respondents (100%) had elevated ESR levels both before and after hemodialysis. In contrast, Hct values decreased following hemodialysis, which is likely due to reduced erythropoietin production associated with CKD, leading to anemia. In conclusion, no significant difference was observed in ESR values before and after hemodialysis. However, there was a notable difference in Hct values, which declined after the procedure.